(untitled) (Scientific journal of the Fergana State University, 2026)
This volitional behavior represents purposefulness, self-control, abstinence from one or another action when a situation arises, that is, mastering one’s own behavior. The ability to control one’s behavior is an important characteristic of an adult. "We are told about personality formation only after acquiring personal behavior